2013
DOI: 10.1155/2013/828754
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Analysis of Traditional Chinese Medical Elongated Needle Therapy on Acute Spinal Cord Injury and Its Mechanism

Abstract: Acute spinal cord injury is one of the most common and complicated diseases among human spinal injury. We aimed to explore the effect of point-through-point acupuncture therapy with elongated needles on acute spinal cord injury in rabbits and its possible mechanism. Adult rabbits were randomly divided into a model group, elongated needle therapy group, and blank group. Immunohistochemical staining showed that the protein levels of Fas and caspase-3 in the model group were significantly higher than those in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…These two pathways eventually converge at caspase-3, which executes apoptosis by cleaving the cytoskeleton and activating DNA-degrading enzymes. Du et al [ 36 ] documented that the penetrating acupuncture at BL54 ( Zhibian ) and ST28 ( Shuidao ) inhibited exogenous death receptor-mediated apoptosis of neurons in acute SCI and downregulated the local expression of FAS and caspase-3. Shi et al [ 37 ] showed that the elongated needle therapy at BL54 and ST28 promoted the recovery from SCI.…”
Section: The Effect Of Acupuncture On Neural Restoration In Spinalmentioning
confidence: 99%
“…These two pathways eventually converge at caspase-3, which executes apoptosis by cleaving the cytoskeleton and activating DNA-degrading enzymes. Du et al [ 36 ] documented that the penetrating acupuncture at BL54 ( Zhibian ) and ST28 ( Shuidao ) inhibited exogenous death receptor-mediated apoptosis of neurons in acute SCI and downregulated the local expression of FAS and caspase-3. Shi et al [ 37 ] showed that the elongated needle therapy at BL54 and ST28 promoted the recovery from SCI.…”
Section: The Effect Of Acupuncture On Neural Restoration In Spinalmentioning
confidence: 99%